Study on Temperature Feedback Effect of Supercritical CO2–Cooled Reactor - Wang, Lianjie; Lu, Di; Yao, Lei; Xiang, Hongzhi; Zhao, Chen (Frontiers in Energy Research, 2021)
As a potential new-type reactor, the supercritical CO2 (S-CO2)–cooled reactor has several advantages, such as being a simple system, having high thermal efficiency, having a small size, and being lightweight. Due to the poor neutronics moderation performance, the S-CO2–cooled reactor shows the disadvantage of a weak temperature feedback effect on reactivity. In this article, the neutronics performance of the reactor has been focused on, and the effects of temperature feedback on fuel, coolant, and moderator studied and the method to improve temperature feedback of the S-CO2 reactor proposed.